The effect of free capital mobility on economic growth in the member countries of the Pacific Alliance, during 2000-2019 - Yunga, Luis (2021)
This research work focuses on the liberalization of capital in the case of the member countries of the Pacific Alliance. This regional integration was formally constituted in 2012 and is made up of Chile, Colombia, Mexico and Peru, among its objectives is to achieve greater development and economic growth, in order to generate greater well-being for its citizens, eradicating the different socioeconomic inequalities existing in the countries. To achieve this, they propose four axes (free movement of goods, services, capital and people). It is important to focus the analysis on the aforementioned group of countries due to the prestige they are having, given that it has observers from countries such as Australia, Canada, Ecuador, Spain, the United States, France, Japan, and China. In addition, the Gross Domestic Product (GDP) as a whole covers more than 35% of the total of Latin America, and they are recipients, on average, around 60 million dollars of Foreign Direct Investment (FDI).